A phenomenological study of the meaning of geography teacher-researcher identities. Issue 1 (2nd January 2020) - Lee, Dong-min
Abstract: The purpose of this study was to interpret the meaning of geography teacher-researcher identities (GTRIs) using van Manen phenomenology. The raw data were obtained through in-depth interviews with nine South Korean geography teacher-researchers (GTRs). The meaningful and significant sentences and phrases were coded into 248 nodes and eventually classified into four themes to interpret the meaning of GTRIs. First, the GTRs continuously engaged in research as they appreciated the potential of academic methodologies and theories to improve the status of geography. Second, their professional identities encouraged the GTRs' continuous engagement in academic activities. Third, the GTRs reported that they produced contextual knowledge and discussions of real contexts for geography education from the perspective of practitioners. Fourth, the GTRs strongly identified as geography teachers and engaged in research based on their teacher identities. The results of this study contribute to a renewed understanding of GTRs' specific meaning and potential in geography teaching and geography education research.